Changes in commissioning home care: an English survey. (24th January 2020) - Davies, Sue; Hughes, Jane; Davies, Karen; Dalgarno, Elizabeth; Jasper, Rowan Elaine; Chester, Helen; Roberts, Amy; Challis, David
Abstract : Purpose: The purpose of this study is to examine changes in the nature, form and range of commissioning arrangements for home care. Design/methodology/approach: Data from two discrete national surveys of English local authorities with social service responsibilities were used. In the first, undertaken in 2007, responses from 111 of the 151 local authorities (74%) were received; in the second, undertaken in 2017, responses from 109 local authorities (72%) were received. A combined data set of 79 complete cases, 52% of local authorities, was created. Percentage point differences across the two time periods were calculated and tested to identify significant changes and a systematic analysis of the free-text responses regarding intended changes to the commissioning process in each data set was undertaken. Findings: Findings identified substantial changes in some aspects of the commissioning of home care in the 2007-2017 decade. Collaboration between stakeholders had increased, particularly regarding the identification of future needs. Improved conditions of service and remuneration for home care workers were evident within the commissioning process. Standardised charges for home care (regardless of time and day) had also become more widespread. Initiatives to prompt providers to deliver more personalised care were more evident. Originality/value: This paper describes the evolution of commissioning arrangements for home care in localities in response to national policy initiatives. It provides guidance to commissioners in meeting the needs of current service users and emphasises the importance of collaboration with stakeholders, particularly providers, in securing future capacity.